2013
DOI: 10.1039/c3cp50424g
|View full text |Cite
|
Sign up to set email alerts
|

Structural investigation of microhydrated thymine clusters and vibrational study of isolated and aqueous forms of thymine using DFT level of theory

Abstract: This theoretical study provides the physically reasonable structures of the microhydrated thymine clusters, from the mono- to the penta-hydrated species, by the exploration of their B3LYP and B3LYP-D potential energy surfaces using a global search algorithm of minima (GSAM). The anharmonic vibrational computations of the isolated and aqueous thymine are also reported. They were performed from B3LYP and B3LYP-D potential electronic surfaces followed by a second order perturbative treatment of the anharmonicity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
22
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 42 publications
1
22
0
Order By: Relevance
“…Two very intense bands were observed at 1690 and 1625 cm À1 for the pH 6.5 solution, whereas only the latter was detected at pH 12. Following previous investigations on similar molecules, 47 the former band was assigned mainly to the C 2 ]O stretching, 47 located at a wavenumber lower than the one usually reported for carbonyl groups (1720-1700 cm À1 ), probably due to the partial single-bond character, related to the tautomerism occurring on the pyrimidine ring. Actually, a contribution due to the NH bending, reported at 1680 cm À1 by Tsuboi et al in their infrared and Raman spectroscopy investigation related to unmodied nucleic acids, 48,49 could not be excluded.…”
Section: Ftir-atr Spectroscopy: 4-thiothymidine Ph-related Featuresmentioning
confidence: 65%
See 1 more Smart Citation
“…Two very intense bands were observed at 1690 and 1625 cm À1 for the pH 6.5 solution, whereas only the latter was detected at pH 12. Following previous investigations on similar molecules, 47 the former band was assigned mainly to the C 2 ]O stretching, 47 located at a wavenumber lower than the one usually reported for carbonyl groups (1720-1700 cm À1 ), probably due to the partial single-bond character, related to the tautomerism occurring on the pyrimidine ring. Actually, a contribution due to the NH bending, reported at 1680 cm À1 by Tsuboi et al in their infrared and Raman spectroscopy investigation related to unmodied nucleic acids, 48,49 could not be excluded.…”
Section: Ftir-atr Spectroscopy: 4-thiothymidine Ph-related Featuresmentioning
confidence: 65%
“…The 1625 cm À1 band has been usually assigned to the C 5 ]C 6 bond stretching observed for thymine and 4-thiouracil. 46,47 The comparison between Fig. 4a and b indicates a very signicant change in the transmittance ratio for the two cited bands when passing from an almost neutral (pH 6.5) to a basic (pH 12) medium, with the C 2 ]O stretching band disappearing completely and the C 5 ]C 6 band becoming predominant.…”
Section: Ftir-atr Spectroscopy: 4-thiothymidine Ph-related Featuresmentioning
confidence: 95%
“…It has been shown that fully anharmonic simulations are required to obtain realistic spectral line-shapes, which are strongly influenced by different intra- and inter-molecular interactions 32,35. Moreover, the B3LYP-D363,64 computations led to remarkable improvements on the accuracy of structural parameters and binding energies for systems involving both stacking interactions and hydrogen bonds, providing at the same time accurate anharmonic frequencies 32,33,46,62,7173. However, some larger discrepancies with respect to experiment are still observed for the X-H and C=X (X=O, N) stretching frequencies32,61, which can be systematically amended by hybrid computations46,74,75 with harmonic frequencies corrected at higher-level of theory (Coupled Cluster (CC) or B2PLYP) with basis sets of at least triple- ζ quality17,46,59.…”
Section: Introductionmentioning
confidence: 99%
“…However, some of the most successful lastgeneration functionals (M06-2X 113 and ωB97X 114,116 ) do not predict vibrational wavenumbers with an accuracy sufficient for spectroscopic studies 31,89,90,117 . On the other hand addition of semi-empirical dispersion corrections to B3LYP (leading to B3LYP-D 109,110 ) showed better promises for accurate computation of vibrational properties for larger weakly bound molecular systems where dispersion/stacking interactions cannot be neglected 31,41,117 . Considering also other B3LYP-based dispersive methods, we have chosen the improved version of Grimme's correction, B3LYP-D3 111,118 coupled to the SNSD basis set and the last version of dispersion-correcting potentials by Di Labio (B3LYP-DCP [119][120][121][122] with the companion 6-31+G(2d,2p) basis set), for calculating anharmonic frequencies of nucleobases and their dimers.…”
Section: Introductionmentioning
confidence: 99%